Reliable It Service Comes with Price - Pratama, Edwin Yoyada (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Many companies are now considering investing in IT projects. The projects they invest in are very expensive. However the project they invested in cannot be assured to be success in the implementation. About 70% of IT projects are failed due to the poor governance. Some of them are failed because of the lack of understanding of the project value. The decision-maker of IT project should realize that IT project are not all about IT; people using the system should also be considered in investing.